Civilized explosive welding: Impact welding of thick aluminum to steel plates without explosives. (December 2018) - Lee, Taeseon; Mao, Yu; Gerth, Richard; Vivek, Anupam; Daehn, Glenn
Graphical abstract: Abstract: In this paper, we report welding of 6.35 mm thick AA5052-H32 and AA1100-H14 plates to mild steel, which was achieved in a laboratory environment by vaporizing foil actuator welding (VFAW). An AA3003-H14 interlayer was used between the AA5052-H32 and the mild steel to improve weldability. The flyer velocity was measured by in-situ photon Doppler velocimetry, and the recorded data provides information about the impact condition and weldability of each material combination. Micro-indentation confirmed that there is no heat affected zone (HAZ) as most conventional welding techniques would produce. Mechanical testing showed that the lap shear strength is comparable to the ultimate tensile strength of the aluminum base plate. We demonstrate VFAW as a viable manufacturing technique for defense and other applications requiring thick aluminum to be joined to steel.